High-resolution and -precision spectra of acetonitrile at the ν5-band for laser remote sensing. (November 2020) - Guan, Hongfei; Wang, Xiaoyu; Han, Ruiyan; Yuan, Liming; Meng, Shuo; Wang, Shuanke; Du, Zhenhui
Highlights: The acetonitrile (CH3 CN) spectra of the v5 -band in the region of 3039.0–3041.5 cm −1 is recorded. The absolute spectroscopic measurements of CH3 CN spectra is performed. Ultrahigh-resolution spectroscopic measurements of CH3 CN in the mid-infrared range using TLAS have been achieved. Abstract: Ultrahigh-resolution and -precision air-broadened acetonitrile (CH3 CN) spectra of the v5 -band in the region of 3039.0–3041.5 cm −1 were recorded and analyzed using tunable laser absorption spectroscopy (TLAS) technology with a distributed feedback interband cascade laser. The spectral line profile of methane (CH4 ) was used as the standard to correct the nonlinearity and baseline drift in the CH3 CN spectra. The recorded spectra are very close to that in the Pacific Northwest National Laboratory (PNNL) database, however it has a much lower absorbance uncertainty of 1.02%. The air-broadened CH3 CN absorption at the v 5 -band with a spectral resolution of 2.15 × 10 −5 cm −1 ( 23 fm/637 kHz) and an estimated uncertainty of 1.1% was derived at a temperature of 296.75 K and a pressure of 1 atm. The ultrahigh-resolution and -precision spectra of CH3 CN provide reference data for absolute spectral measurements, laser remote sensing, and atmospheric inversion.